Temperature-Dependent Magnetic Properties of Ni Nanotubes Synthesized by Atomic Layer Deposition - Escrig-Murua, J; Palma-Solorza, J; Pereira-Abarca, A; Casagrande-Denardin, J (Institute of Physics Publishing, 2016)
Highly-ordered and conformal Ni nanotube arrays were prepared by combining atomic layer deposition (ALD) in a porous alumina matrix with a subsequent thermal reduction process. In order to obtain NiO tubes, one ALD NiCp2/O3 cycle was repeated 2000 times. After the ALD process, the sample is reduced from NiO to metallic Ni under hydrogen atmosphere. Their magnetic properties such as coercivity and squareness have been determined in a vibrating sample magnetometer in the temperature range from 5-300 K for applied magnetic fields parallel and perpendicular to the nanotube axis. Ni nanotubes synthesized by ALD provide a promising opportunity for potential applications in spintronics, data storage and bio-applications. © 2016 IOP Publishing Ltd.